If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 10 + -3 = 4x Combine like terms: 5 + 10 = 15 15 + -3 = 4x Combine like terms: 15 + -3 = 12 12 = 4x Solving 12 = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 12 + -4x = 4x + -4x Combine like terms: 4x + -4x = 0 12 + -4x = 0 Add '-12' to each side of the equation. 12 + -12 + -4x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -4x = 0 + -12 -4x = 0 + -12 Combine like terms: 0 + -12 = -12 -4x = -12 Divide each side by '-4'. x = 3 Simplifying x = 3
| (3x+50)=(7x-10) | | 2y+4=x-10 | | 6b-12=10+8b-4b | | 3(2y-5)= | | 2(x^3-3x^2-3x+9)=0 | | 5y^2-4x^2=20 | | 30a^2b^3c^4-20a^5b^2c^3+10a^3bc^2= | | (6y-16)=(4y+6) | | a+b=4 | | 3r-2+5r=2r+12 | | 10x+3y-9=0 | | (Y-4)(y-7)= | | 6x-13=2x-5 | | 3x-18=x+10 | | w^2+16=8w | | 2x+5x=3.5 | | 10y+2=x-6 | | (2b)2= | | [5.6]= | | 3u^2-11u=4 | | [-2/3]= | | 5r(4r-5)=0 | | [-9]= | | 12x-29=79 | | 10x+1=9x-x+3 | | [8]= | | 2ab*4b= | | 7-5z=6z-26 | | 3z^2-3z-6=0 | | 13x+7=215 | | 28m^4-14m^3+7m^2= | | 4x-9=3.5x-9 |